KEMAMPUAN MENEMUKAN IDE POKOK PARAGRAF BERBAGAI JENIS WACANA DALAM NASKAH SOAL UN OLEH SISWA KELAS X SMA SATRIA NUSANTARA BINJAI TAHUN PELAJARAN 2012/2013 - DELI GUSMIATI (Kode : Jurnal Bahasa, 2014)
This study aims to describe the students’ ability to find the main ideas ofparagraph in writing of UAN by the ten Grades of students’ of SMA Satria NusantaraBinjai in Academic Year 2012/2013, which amounted to 200 students and that asample as many as 30 students. Sampling was done by determining the class to berepresentative of the population studied. The research method used was descriptivemethod which describe the phenomena of the real situation. The test was given bythe students through objective test which consists of 20 items. It consists ofdescriptive, narration, argumentation, persuasion, and exposition. To analyze thestudents’ ability to find the main idea, it was used the percentage as in the following.x 100%nfiPi The findings indicate that the students’ ability of ten Grade students of Senior HighSchool in Academic Year 2012/2013 to find the main ideas of paragraph in UAN wascategorized Good, where the means score of the students’ 70,33. From the 5 kinds ofwriting, descriptive writing was easy to be understood by the students. It was provedfrom 106 or 24.82% and the persuasion writing is more difficult for the students. Itwas proved 60 or 14,51%.Keywords: students’ ability, main ideas, paragraph.